2016
DOI: 10.1590/1982-3703000342014
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do Trabalho em Profissionais de Serviços de Saúde Mental em um Município do Nordeste Brasileiro

Abstract: Work impact on professionals from mental health services in a Brazilian northeast cityAbstract: The aim of this study was to evaluate the work impact felt by health professionals dealing with people who have psychiatric disorders. This is a field research on a quantitative approach. Data collection occurred through the Impact Assessment for Mental Health Services tool applied to 87 mental health professionals in the city of Natal, Brazil. The results show a low overhead effect on the professionals surveyed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…However, such problems do not affect all the professionals who daily deal with psychiatric patients. Similarly to other professionals who work in psychiatry, also they tend to develop mental disorders derived from their work 3 . The approach to mental diseases that result from excessive work and the cognitive and emotional overload derived from the nature and efficacy of tasks and the conditions under which they are performed should focus on the health and feelings of workers.…”
Section: Introductionmentioning
confidence: 99%
“…However, such problems do not affect all the professionals who daily deal with psychiatric patients. Similarly to other professionals who work in psychiatry, also they tend to develop mental disorders derived from their work 3 . The approach to mental diseases that result from excessive work and the cognitive and emotional overload derived from the nature and efficacy of tasks and the conditions under which they are performed should focus on the health and feelings of workers.…”
Section: Introductionmentioning
confidence: 99%
“…A study that applied the Brazilian Mental Health Services' Satisfaction Scale (IMPACTO-BR), which evaluates the overload felt by mental healthcare professionals as a consequence of daily work, associated the work impact with some sociodemographic and occupational characteristics in the sample, with a prevalence of: women, complete high school, work carried out in shifts, and a shorter time working in the institution. Professionals between 25 and 39 years old showed a higher impact on their health when faced with the intensification of feelings such as frustration, overload, stress, depression, and feeling tired after work (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gender, studies involving health workers have associated the "female gender with MPD" (2,(8)(9)(10)(11) . Among the nursing professionals who worked at a hospital, logistic regression analysis showed that "women had a 2.36 higher probability to have MPD and, among those younger than 39 years, the chances were 2.21 times higher" (3) .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, mental health services produce situations that affect health conditions, in particular, of nursing professionals. These situations increase the risks of illness associated with the feeling of physical fatigue at the end of the work day, caused by the fear of suffering some kind of aggression by users (3) , exposure to physical and psychic loads, inadequate working conditions, limitation of autonomy, stress complaints, body aches, anxiety and fatigue, leading to suffering at work (4) .…”
Section: Introductionmentioning
confidence: 99%